Successful diagnosis and treatment of ingested wooden toothpicks: Two case reports. Issue 5 (February 2018) - Lin, Nan; Lin, Li; Wu, Weihang; Yang, Weijin; Cai, Zhicong; Hong, Jie; Wang, Yu
Abstract: Rationale: Foreign-body ingestion is a common phenomenon and foreign bodies are mostly excreted in stool. Once sharp bodies are ingested without being realized, perforation of intestine is possible and misdiagnosis may be made. We report 2 toothpick ingestion cases that were both diagnosed accurately. Patient concerns: We present 2 cases of middle-aged persons who suffered from abdominal pain. They did not realize and provide any information of having the history of swallowing foreign bodies. Diagnoses: No serious problem was discovered in the examination and blood test. There were somewhere abnormal in computed tomography (CT) images and ultrasound (US). Then a toothpick was found penetrating the wall of intestine into the adjacent viscera in the laparotomy. Interventions: Both patients in the 2 cases were undergone operation to remove the toothpicks. Outcomes: The 2 cases' prognoses were good. Lessons: When accepting patients with abdominal pain, suitable examining means and careful observation should be given to find easily ignored lesions. CT is recommended in the diagnostic process of swallowed foreign mass. When there is a vague place, US can be used for further diagnose.